2021
DOI: 10.5194/amt-14-1111-2021
|View full text |Cite
|
Sign up to set email alerts
|

MUCCnet: Munich Urban Carbon Column network

Abstract: Abstract. In order to mitigate climate change, it is crucial to understand urban greenhouse gas (GHG) emissions precisely, as more than two-thirds of the anthropogenic GHG emissions worldwide originate from cities. Nowadays, urban emission estimates are mainly based on bottom-up calculation approaches with high uncertainties. A reliable and long-term top-down measurement approach could reduce the uncertainty of these emission inventories significantly. We present the Munich Urban Carbon Column network (MUCCnet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 33 publications
1
61
0
Order By: Relevance
“…Several successful field campaigns and long-term deployments have demonstrated that the Bruker EM27/SUN FTIR spectrometer is an excellent instrument with good quality, robustness and reliability and its performance offers the potential to support TCCON (Frey et al, 2015 andKlappenbach et al, 2015;Chen et al, 2016;Butz et al, 2017;Sha et al, 2019;Jacobs et al, 2020;Tu et al, 2020a and2020b;Dietrich et al, 2021). The Bruker EM27/SUN spectrometers have become commercially available from April 2014 onwards and currently about 70 spectrometers are operated by different working groups in Germany, France, Spain, Finland, Romania, USA, Canada, UK, India, Korea, Botswana, Japan, China, Mexico, Brazil, Australia and New Zealand.…”
Section: Coccon Xch4 Data Setmentioning
confidence: 99%
See 1 more Smart Citation
“…Several successful field campaigns and long-term deployments have demonstrated that the Bruker EM27/SUN FTIR spectrometer is an excellent instrument with good quality, robustness and reliability and its performance offers the potential to support TCCON (Frey et al, 2015 andKlappenbach et al, 2015;Chen et al, 2016;Butz et al, 2017;Sha et al, 2019;Jacobs et al, 2020;Tu et al, 2020a and2020b;Dietrich et al, 2021). The Bruker EM27/SUN spectrometers have become commercially available from April 2014 onwards and currently about 70 spectrometers are operated by different working groups in Germany, France, Spain, Finland, Romania, USA, Canada, UK, India, Korea, Botswana, Japan, China, Mexico, Brazil, Australia and New Zealand.…”
Section: Coccon Xch4 Data Setmentioning
confidence: 99%
“…Due to the ruggedness of the portable devices used and simple operability, COCCON is well suited for implementing arrays of spectrometers for the quantification of local GHG sources (Hase et al, 2015;Luther et al, 2019;Vogel et al, 2019;Dietrich et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Observational networks such as the Utah Urban Carbon Dioxide Network (UUCON) and mobile rail‐based (TRAX) measurements in Salt Lake City, UT (Bares et al., 2019; Mitchell, Crosman, et al., 2018), the Indianapolis Flux Experiment (INFLUX) in Indianapolis, IN (Richardson et al., 2017), the Berkeley Environmental Air Quality & CO 2 Network (BEACON) in San Francisco, CA (Shusterman et al., 2016), the Los Angeles Megacity Carbon Project in Los Angeles, CA (Verhulst et al., 2017), and the Munich Urban Carbon Column Network (MUCCnet) in Munich, Germany (Dietrich et al., 2021) all provide insights into the spatiotemporal dynamics of these urban emissions. It is often the case that urban emissions produce atmospheric CO 2 concentrations that are measurably higher than regional baseline values (Jacobson, 2010; Wang & Ostoja‐Starzewski, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The core instruments of the campaign were two portable FTIR (Fourier Transform InfraRed) spectrometers (Bruker EM27/SUN) which were used for ground-based remote sensing measurements of the total column amount of CO 2 , CH 4 and CO at upwind and downwind locations on opposite sides of the city. The applicability and efficiency of this measurement scenario and EM27/SUN spectrometers have been shown by Hase et al (2015), Chen et al (2016) and Dietrich et al (2021). The description of the EMME experiment has been given in full detail in the paper by Makarova et al (2021).…”
mentioning
confidence: 99%